El vínculo reparador entre los niños deprivados y las instituciones de protección social (2014)
ABSTRACT: The objective of the study was to identify the relational experiences who allow the establishment of a repair link, between deprived children and social protection institutions that host them. A qualitative methodology was used assuming the postulates of the interpretive paradigm. The sample consisted on 20 institutionalized childrens who lived a situation of deprivation in early childhood and the care team two institutions for the protection. The instruments used with children were the semi-structured interview and application of T.A.T projective test and the Family Drawing Test. Were realized group interviews with the care team of the institutions. In the results, the repair link is presented as an intersubjective process that explains the psychological dynamics of the repair in the context of protection institutions. Different forms of deprivation were found, the particularity of each one influences the acceptance or rejection of the repair by the child, in the way of relating to the institution and in developing and strengthening their own repair capacity. The role of protection institutions is differentially analyzed from two dimensions: The restorative repair and the subjective repair.